Pso-based Pid-pd Controller of a Gantry Crane with Parameter Uncertainties - Zaki Hakimi Ab Rahim; Muhamad Rafyq Roslan; Liyana Ramli; Izzuddin M Lazim (Penerbit UMT, 2024)
Indexed by Scopus/ERA/MyCite